أثر تعلم اللغة باستخدام الحاسوب في اتجاھات الطالبات نحو الأستیعاب - Iman Muwafaq Muslim (College of Education for Women, 2019)
Abstract The study is the product of an on-line session with Oregon University. It aims at developing the students' attitudes toward using computers in learning to get the advantages of CALL and autonomous learning. The researcher has depended on a one-group design of a pre-scale and post-scale to measure the effect due to exposure to computer using.